Measuring mRNA Decay with Roadblock‐qPCR. Issue 1 (18th January 2022) - Watson, Maegan J.; Thoreen, Carson C.
Abstract: The control of mRNA stability is fundamental to gene regulation, and a deeper understanding of this post‐transcriptional regulatory step can provide key insights into gene function. Measuring mRNA half‐lives directly, however, is challenging. The most common strategies for evaluating mRNA stability and decay involve blocking general transcription and then measuring the decline in mRNA levels over time. The downside of these approaches, however, is that they severely impact cell function and viability, indirectly perturbing gene expression. Here, we describe Roadblock‐qPCR, a simple method for measuring mRNA decay kinetics in living cells that is both economical and quick. Cells are first incubated with the nucleoside analog 4‐thiouridine (4sU), which is readily incorporated into nascent mRNAs during transcription. RNA is then extracted and treated with N‐ ethylmaleimide (NEM), a sulfhydryl alkylating agent that selectively modifies 4sU, before proceeding to cDNA synthesis. Because the NEM‐modified 4sU creates a chemical "roadblock" that interferes with reverse transcription, this treatment ultimately results in the depletion of the nascent 4sU‐containing transcripts from the cDNA pool. As such, the decay rate of the non‐4sU‐labeled pre‐existing mRNAs can be monitored by quantitative PCR (qPCR). In combination with spike‐in standards, this approach can be used to efficiently and accurately measure the half‐lives of endogenous mRNAs with a wide range of stabilities, while avoiding the artifacts of transcription shutoff strategies. © 2022 Wiley Periodicals LLC. Basic Protocol : Roadblock‐qPCR Support Protocol : Synthesis of spike‐in mRNA